Desenvolvimento de bolos, com e sem adição de açúcar, a partir da substituição parcial da farinha de trigo por farinha de casca e semente de abóbora (Cucurbita moschata) - Silva, Janaína Valéria da (2011)
A healthy diet, prepared without waste and with the inclusion of functional ingredients is important for improving the quality of life of individuals. Thus, the use of shares which are not usually edible pumpkin seeds and skins as it may be beneficial for consumers due to the levels of β-carotene, fiber, proteins, lipids and carbohydrates such waste. Thus, the purpose of this study was to develop a cake, with and without added sugar, with partial replacement of wheat flour by flour shell and seed pumpkin (Cucurbita moschata). Initially, we used Response Surface Methodology associated a 23 factorial design, optimized to the levels of addition of flour and husk pumpkin seed, and sugar added to the cake. The response variables were the cakes acceptability with regard to the sensory attributes of appearance, aroma, flavor, texture and overall acceptability. The centesimal composition as well as the contents of β−carotene and vitamin A were determined in the flours of the pumpkin’s peel and seed, in the optimized formulation of the cake enriched with flour of the pumpkin’s peel and seed, and in the standard cake produced with pure wheat flour. Finally, from the optimized formulation of the cake flour enriched with flours of the pumpkin’s peel and seed, six different diet cake formulations were developed using three commercial sweeteners: stevia, a mixture of sucralose with acesulfame K, and a mixture of saccharin and cyclamate. In pumpkin seed flour stood out the protein (34%) and lipids (39%). The fiber content of flour present in the bark (8.6%) and pumpkin seed (12.3%) allows the two products are classified as "high level"of fibers, according to current Brazilian legislation. High levels of vitamin A were found in both the peel flour and pumpkin seed. The optimized cake, prepared by replacing 35% wheat flour by 17.5% shell meal and 17.5% of pumpkin seed flour had good acceptance among consumers and was rich in fiber (3,7%) and vitamin A (3392.42 µg / RE) can be classified as a 'high level ' of vitamin A in accordance with the legislation. Among the diet formulations developed, - the cakes containing stevia, with or without addition of polydextrose, obtained higher overall acceptability and purchase intent among the consumers without diabetes, although this difference was not significant (p > 0.05) comparatively the other formulations. The preferences of diabetic patients in relation to the diet cakes were not evident, but this segment showed higher values of acceptability (p ≤ 0.05) for the dietetic cakes than the non-diabetic consumers.